2017
DOI: 10.4187/respcare.05194
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Autogenic Drainage on Ventilation Inhomogeneity in Adult Subjects With Stable Non-Cystic Fibrosis Bronchiectasis

Abstract: In adults with non-cystic fibrosis bronchiectasis and mucus hypersecretion, autogenic drainage improved ventilation inhomogeneity. LCI change may be the result of the maximum recruited lung volume and the amount of cleared mucus secretion. (ClinicalTrials.gov registration NCT02411981.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
(48 reference statements)
0
9
0
1
Order By: Relevance
“…Thus, we could hypothesize that reducing sputum in the lungs would improve vital capacity. However, even though a recent study in bronchiectasis observed such an effect, 40 it was rarely found with other airway clearance techniques in subjects with CF. [41][42][43] In this systematic review, we did not find any benefit of IPV on airway clearance, contrary to what was demonstrated in subjects with Duchenne muscular dystrophy.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, we could hypothesize that reducing sputum in the lungs would improve vital capacity. However, even though a recent study in bronchiectasis observed such an effect, 40 it was rarely found with other airway clearance techniques in subjects with CF. [41][42][43] In this systematic review, we did not find any benefit of IPV on airway clearance, contrary to what was demonstrated in subjects with Duchenne muscular dystrophy.…”
Section: Discussionmentioning
confidence: 74%
“…Grosse‐Onnebrink et al 36 demonstrated a significant decrease in LCI 2.5 after the high‐frequency chest wall oscillation technique was used on CF patients; the effects of that technique were similar to ours (median change in LCI 2.5 = −0.9). Poncin et al 37 showed improvements in LCI 2.5 and slow vital capacity after autogenic drainage in adults with non‐CF bronchiectasis. Other studies have shown no significant short‐term effects of established therapeutic approaches on ventilation inhomogeneity 38–40 …”
Section: Discussionmentioning
confidence: 99%
“…6 This is probably due, in part, to poor adherence to airway clearance techniques by patients with airway disease. 8 From this study, 7 it appears that the patients most likely to benefit from incorporating autogenic drainage into their daily routine are those with primary ciliary dyskinesia and significant sputum expectoration. There may also be a role for autogenic drainage in patients with other forms of bronchiectasis who also have significant expectoration.…”
mentioning
confidence: 88%
“…5 There are few published studies evaluating autogenic drainage in subjects with diseases other than cystic fibrosis, a common problem in all studies of airway clearance techniques. 6 In this issue of RESPIRATORY CARE, in a paper by Poncin et al 7 from Belgium, the home of autogenic drainage, it is reported that in subjects with non-cystic fibrosis bronchiectasis, lung clearance index (a measure of ventilation SEE THE ORIGINAL STUDY ON PAGE 524 homogeneity) improved after autogenic drainage, but improvement was only seen in 20% of the subjects studied. There was no improvement in pulmonary function other than a modest change in slow vital capacity.…”
mentioning
confidence: 99%